PENGARUH EMPLOYER BRANDING, CORPORATE REPUTATION, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP INTENTION TO APPLY JOB PADA GEN Z - Wardani, Rica Aprilia; Ikhram, M. Abdi Dzil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the effects of employer branding, corporate reputation, and corporate social responsibility on the intention of Gen Z to apply for job. The respondents of this quantitative explanatory research are 380 undergraduate students of Faculty of Economics and Business of Universitas Brawijaya; they were selected using simple random sampling technique. The research data was harvested from Likert-scaled questionnaires that have been tested using validity, reliability, and classical assumption tests. The research hypotheses were assessed using t-test, and the analysis were conducted using multiple linear regression; all of which were performed in SPSS. This study finds that employer branding, corporate reputation, and corporate social responsibility have partial effects on the intention of Gen Z to apply for job. Furthermore, the factor or indicator of corporate social responsibility that has the most effect is stakeholder dimension.